EXPLORING THE MEDIATING ROLE OF PATIENT SATISFACTION IN THE RELATIONSHIP BETWEEN PHARMACY SERVICE PERFORMANCE AND PATIENT LOYALTY - Tris Yulianti; Hery Winoto TJ (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Abstract— The Study aims to analyze the effect of drug availabity and prescription waiting time on patient loyalty , with patient satisfaction as a mediating variable in the outpatient pharmacy unit. The main issues in outpatient pharmaceutical services include limited drug availability and log prescription waiting times, which may reduce patient satisfaction and ultimately impact patient loyalty. This research employs a quantitative approach using a survey design. Data were collected through questionnaires distributed to outpatient who had received pharmacy services. The sampling technique used was purposive sampling based on specific criteria. Data analysis was conducted using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach to examine the relationships among variable. A total of 100 respondents participated in this study. Drug availability significantly influenced patient satisfaction (p=0.000) and patient loyalty (p=0.006 ), whereas prescription waiting time had significant negataive effects on patient satisfaction (p =0.000), and patient loyalty (p=0.128 ) Patient satisfaction partially medicated both relationships.